PENGARUH ANGKA BEBAS JENTIK TERHADAP KEJADIAN PENYAKIT DBD TAHUN 2021: Studi Kasus di Wilayah Kerja Puskesmas Perak Kabupaten Jombang - Firda Yusy; Marlik; Irwan Sulistio (Gema Lingkungan Kesehatan, 2022)
Perak Health Center has the highest incidence of dengue cases in Jombang. Mosquito nest eradication activities in the Perak Health Center's working area are not optimal, seen from the larva free rate which is still below 95%. The purpose of the study was to determine the effect of ABJ on the incidence of DHF in the Work Area of ​​the Perak Health Center, Jombang Regency. Observational analytical quantitative research with an evaluation approach using Spearman correlation test data processing to determine the effect of ABJ on DHF cases in Perak Health Center. The data was processed from January 2019 to December 2020. The ABJ value at the Perak Health Center in 2019-2020 is 86-90%, increasing during the dry season and decreasing during the rainy season. DHF cases ranged from 0-22.22%, the highest occurred in the rainy season and decreased during the dry season. The results of the correlation test showed that the value of P = 0.617 > showed that there was no effect between ABJ and DHF cases at the Perak Health Center. The ABJ value at the Perak Health Center increases during the dry season, and vice versa. The highest cases of DHF occur in the rainy season. The ABJ value has no effect on the incidence of DHF at the Perak Health Center. The researcher recommends that the vector control program must be improved so that the ABJ value can be in accordance with government regulations (≥95%) and the number of DHF cases can be further suppressed.